L’attirail de la titraille. Morphosyntaxe des désignants d’événement dans les titres de presse - Calabrese, Laura; Roig, Audrey; Van Raemdonck, Dan (Neophilologica, 2014)
This paper analyses the place of event names in newspaper headlines from a morphosyntactic point of view. We address the hypothesis that titles including event names are structured like phrases. We will describe the titles in terms of topic/comment, topic-area/comment-area and subject/predicate, to show that events are thematized after being synthetized by media discourse. We will also address the question of the role event names play in the title, whether in the thematic area or an enunciation determiner.